Study of Nanocellulose Fibrils. Derived from Bioresource Waste: Reduction of Agglomeration and Cross-linking. - Yhaya, Mohd Firdaus (Universiti Sains Malaysia, 2016)
The research was intended to study the nanofibrils obtained from bioresource waste (palm oil empty fruit bunches). The azide-alkyne click chemistry was used as a tool to modified the nanofibrils. It was found that both attachment of bulky substituents and non-polar substituents prevented the agglomeration of nanofibrils.